Comparative In Vitro Activities of First and Second-Generation Ceragenins Alone and in Combination with Antibiotics Against Multidrug-Resistant Klebsiella pneumoniae Strains - Berna Ozbek-Celik; Damla Damar-Celik; Emel Mataraci-Kara; Cagla Bozkurt-Guzel; Paul B. Savage (MDPI AG, 2019)
Objectives: The ceragenins, or CSAs, were designed to mimic the activities of antimicrobial peptides and represent a new class of antimicrobial agent. The aim of this study was to comparatively investigate the antimicrobial activities of first/second generation ceragenins and various antibiotics against multidrug-resistant (MDR) Klebsiella pneumoniae, including colistin-resistant bacteria. Also, the synergistic effects of two ceragenins with colistin or meropenem were investigated with six K. pneumoniae strains presenting different resistant patterns. Methods: Minimal inhibition concentrations (MICs) were determined by the microdilution method according to the CLSI. Antibiotic combination studies were evaluated by the time−kill curve method. Results: MIC50 and MIC90 values of tested ceragenins ranged from 8 to 32 mg/L and 16 to 128 mg/L. Overall, among the ceragenins tested, CSA-131 showed the lowest MIC50 and MIC90 values against all microorganisms. The MICs of the ceragenins were similar or better than tested antibiotics, except for colistin. Synergistic activities of CSA-131 in combination with colistin was found for strains both at 1× MIC and 4× MIC. No antagonism was observed with any combination. Conclusions: First-generation ceragenins CSA-13 and CSA-44 and second-generation ceragenins CSA-131, CSA-138 and CSA-142 have significant antimicrobial effects on MDR K. pneumoniae. Mechanisms allowing resistance to clinical comparator antibiotics like colistin did not impact the activity of ceragenins. These results suggest that ceragenins may play a role in treating infections that are resistant to known antibiotics.